Współpraca transgraniczna i regionalna w obszarze Morza Bałtyckiego w latach 1989-2007 - Czerniak, Robert (My University, 2010)
Cross-border and regional cooperation in the Baltic Sea area in the years 1989-2007. Political changes, accomplished after the year 1989 in the Baltic Sea area, allowed to raise relationship between countries, regions and enabled easier contact between people living in that area. The collapse of artificial partitions existing after the Second World War in the Baltic Europe became the crucial factor in the development of multilateral connection between governments, organizations, regions and all types of local governments and no governments` organizations in the 1990s. Nowadays the term of the hibernation of the region is a part of history and a warning in creating partnership between countries which now belong to the European Union and Russia.The subject is not the accidental one. The Baltic Sea area its potential on the field of cooperation and development in the extended European Union and relationships between European Union and Russia are the main author’s interests. The foundation of this is the analysis of the regional partnership on the field of social, economical and political cooperation. Looking back at the history of the region, understanding the international relationship and partnership and the cooperation between the European Union and Russia can allow us to find the way the Baltic Europe is getting at. You can also find here the analysis of the relationship, way of development and vision of the future connections between the European Union and Russia. The richness of different forms of cooperation between government and no government’s organizations in the Baltic Sea region, as nowhere else in Europe, should be consolidated by the considered schedule of social, economical and political development. The answer for this postulate, in my opinion, is the strategy of “Northern Dimension” Which creates a bridge for cooperation in the region between the countries which belong to the European Union and those which are not able to join it in the nearest future, for instance, Russia. The Baltic Europe has at its disposal a huge potential. Nowadays the Baltic Sea is the “internal sea” of the European Union. We can estimate that in the nearest decade this area will become one of the fastest developing regions all over the world. It is worth emphasizing this region has highly developing economy, stable and well-educated society and its countries have at their disposal rich natural resources, especially energetic ones. In this area there are magnificent conditions for investment and business development. Therefore, the Baltic Sea region consolidates all these elements in its possibility of cooperation. The Baltic partnership is a cooperation of countries, regions and international and regional organizations. Besides Sweden, Denmark, Finland, Poland, Germany, Lithuania, Latvia, Estonia, which are the European Union members, there is Norway in the region as an economic partner of the European Union in the project of the European Economic Area. Iceland is another country being outside the Baltic Sea Region but it has its influence on international cooperation development in this area. The whole cooperation is complemented by Russia, which is an important partner for the countries of the region and the whole European Union.Organizations are also an important element of the Baltic cooperation. The leading role in the region is performed by Council of the Baltic Sea States (CBSS) – the main forum of the Baltic countries` cooperation. Therefore, some other government organizations have their influence on the Baltic cooperation, for instance, Nordic Council of Minister (NCM), Barents Euro-Arctic Council (BEAC), Arctic Council. In the region there are some subregional organizations, which act dynamically, for instance, Baltic Sea States` Sub-regional Cooperation (BSSSC), Union of the Baltic Cities (UBC) and Helsinki Commission (HELCOM). Euroregions like Pomerania, Baltic, Niemen, perform a very important role in Baltic cooperation building and also some other cross-border cooperation Baltic organizations. The Baltic Sea Region, despite its complicated past, is able to show its unity and identity. A lot of possibilities are also given by the rich net of decentralized organizations and institutions which complement and support official government structures and strong political involvement of the European Union noticeable in European Commission membership in Council of the Baltic Sea States. Russia – European Union partnership, which is connected with this region, should be seen as an opportunity to consolidate our multilateral relations.
Cross-border and regional cooperation in the Baltic Sea area in the years 1989-2007
Wydział Nauk Politycznych i Dziennikarstwa
Keywords: współpraca transgraniczna; cross-border cooperation; Morze Bałtyckie; Baltic Sea